'YET NONE WITH TRUER FERVOUR SING': CORONATION SONG AND THE (DE)COLONIZATION OF AFRICAN CHORAL COMPOSITION - Lucia, Christine (International Library of African Music, 2017)
In 1937, the Se(Sotho) composer, Mohapeloa published 'Coronation Song' a short a cappella choral work that celebrates the coronation of King George VI and which is ostensibly rooted in his colonial experience of the British Protectorate of Basutoland. It was reprinted in Morija in 1939 as 'Coronation March', by which time it was clear that this song's political message was at odds with his other songs. Reprinted in 1945, 55, 66, and 80 with minor changes, the song becomes increasingly anachronistic. Mohapeloa suddenly rewrote it in the mid 1970s, 10 years after Lesotho gained independence, by transforming it into a patriotic song, 'Lesotho Our Heritage' ('Lesotho Lefa la RÅna'). This article traces the song's journey through decades of political change by means of a close hermeneutic reading of its text, musical language and structure, arguing that the music had always identified with two political tendencies, the one European and colonizing, the other American and decolonizing. It was this ambiguity that kept Mohapeloa's interest and led to his last version of the song, finally published only in 2015.
Keywords: Harmony; Decolonisation; Choral music; Colonisation; Colonies; Coronation Song; Basutoland; Lesotho; African Music; Choral Composition